Characterization of enzyme-liqueﬁed soursop (Annona muricata L.) puree - Mohd Ghazali, Hasanah; Chang, Lee Sin; Karim, Roselina; Mohammed, Abdulkarim Sabo (Academic Press, 2018)
Soursop (Annona muricata L.) is a tropical fruit that undergoes rapid postharvest deterioration. Conversion into puree is a way to value add the fruit. Pectinex® Ultra SP-L, Celluclast® 1.5 L, and Fungamyl® 800 L (0–5% v/w) were used to treat fruit pulp and pectinase at 1.5% (v/w) concentration was chosen as the primary enzyme in combined enzymes study because it produced the best result in liquefaction. A liquefied puree with reduced viscosity of up to 50% (15.20 ± 0.17 mPas) was obtained when pectinase was used in combination with cellulase compared to puree treated with pectinase only. Physicochemical results showed the addition of cellulase did not lead to significant changes (P > 0.05) in pH, titratable acidity, and ascorbic acid but caused significant increases (P ≤ 0.05) in total soluble solid and total sugar content. Aroma profile analyzed using a zNose™ showed at least 15 volatile compounds were detected in fresh soursop fruit with methyl hexanoate (MH) (0.023 ± 0.004%) and methyl trans-2-hexenoate (MTH) (0.014 ± 0.002%) as the major volatile compounds. Principal Component Analysis (PCA) indicated six important variables were selected as the principle component which generated total cumulative variance of 92.9%.